Chto Takoe Sovetskaya Diaspora? Is There a Living and Ideologically Sovieticized 'Soviet Diaspora'?. Issue 4 (4th July 2022) - Yapıcı, Utku
ABSTRACT: Throughout its history, the term 'Soviet Diaspora' has been used to describe different groups of people in different contexts and the use of the term 'Soviet Diaspora' has always been controversial. By December 1991, the Union of Soviet Socialist Republics (USSR) ceased to exist but the use of the term 'Soviet Diaspora' has continued in several contexts. This article tries to analyse different uses of the term 'Soviet Diaspora' historically and answer the question of whether there is a living and ideologically Sovieticized 'Soviet Diaspora' or not.